Effect of Particle Size and Pressure on the Transport Properties of the Fast Ion Conductor t‐Li7SiPS8. Issue 15 (3rd March 2023) - Schneider, Christian; Schmidt, Christoph P.; Neumann, Anton; Clausnitzer, Moritz; Sadowski, Marcel; Harm, Sascha; Meier, Christoph; Danner, Timo; Albe, Karsten; Latz, Arnulf; Wall, Wolfgang A.; Lotsch, Bettina V.
Abstract: All‐solid‐state batteries promise higher energy and power densities as well as increased safety compared to lithium‐ion batteries by using non‐flammable solid electrolytes and metallic lithium as the anode. Ensuring permanent and close contact between the components and individual particles is crucial for long‐term operation of a solid‐state cell. This study investigates the particle size dependent compression mechanics and ionic conductivity of the mechanically soft thiophosphate solid electrolyte tetragonal Li7 SiPS8 ( t ‐LiSiPS) under pressure. The effect of stack and pelletizing pressure is demonstrated as a powerful tool to influence the microstructure and, hence, ionic conductivity of t ‐LiSiPS. Heckel analysis for granular powder compression reveals distinct pressure regimes, which differently impact the Li ion conductivity. The pelletizing process is simulated using the discrete element method followed by finite volume analysis to disentangle the effects of pressure‐dependent microstructure evolution from atomistic activation volume effects. Furthermore, it is found that the relative density of a tablet is a weaker descriptor for the sample's impedance compared to the particle size distribution. The multiscale experimental and theoretical study thus captures both atomistic and microstructural effects of pressure on the ionic conductivity, thus emphasizing the importance of microstructure, particle size distribution and pressure control in solid electrolytes. Abstract : Understanding particle mechanics of granular solid electrolytes is critical for all‐solid‐state battery technology. Particle size, as well as applied pelletizing and stack pressure affect measured ionic conductivity of the fast lithium ion conducting glass‐ceramic Li7 SiPS8 . Supporting discrete element and ab initio molecular dynamics simulations shed light on the microscopic and atomistic consequences of powder compression.